Circular economic development in Vietnam - VU, DANG HOANG; SON, DO THE; HOAI, HOANG THI THU; TU, VU THI CAM; THU, VU THI HANH (The journal of contemporary issues in business and government, 2021)
In Vietnam, economic activity has so far been mainly based on the traditional approach, which is linear economy. This is also the basic cause leading to the shortage of natural resources and especially causing serious environmental pollution. In order to realize rapid and sustainable development, to harmoniously deal with the relationship between economic growth and environmental protection, to "do not trade off" economic growth with environmental pollution and degradation, to switch to an eco-friendly economy. circular economy is the right direction. However, this transformation requires seizing the opportunities and accepting the challenges that need to be overcome. The article analyzes opportunities and challenges of circular economy development and proposes solutions to promote circular economy development for Vietnam in the coming time.